The Impact of Simulated Medical Consultations on the Empathy Levels of Students at One Medical School - Schweller, Marcelo (Acad Med, 2014)
PURPOSE: To examine the impact of simulated medical consultations using standardized patients (SPs) on the empathy levels of fourth- and sixth-year students at the Unicamp medical school in Brazil. METHOD: Throughout 2011 and 2012, the authors conducted this study with two classes of fourth-year (n = 124) and two classes of sixth-year (n = 123) medical students. Students completed the medical student version of the Jefferson Scale of Physician Empathy before and after simulated medical consultations with SPs, followed by an in-depth debriefing dealing with the feelings of the patient about the disease, such as fear, guilt, anger, and abandonment; the feelings of the doctor towards the patient; and other topics as they arose. RESULTS: The simulation activity increased the empathy scores of the fourth-year students (from 115.8 to 121.1, P < .001, effect size = 0.61) and of the sixth-year students (from 117.1 to 123.5, P < .001, effect size = 0.64). CONCLUSIONS: Although the study results were obtained via self-report—a limitation—they suggest that the effective simulation of medical consultations with SPs may improve medical students’ empathy levels. One unexpected result was that this activity, during the debriefing, became a forum for debating topics such as the doctor–patient relationship, the hidden curriculum, negative role models, and emotionally significant experiences of students in medical school. This kind of activity in itself may influence young doctors to become more empathetic and compassionate with their patients and foster a more meaningful way of practicing medicine.